A Companion to Plautus - Franko, George Fredric (Blackwell Companions to the Ancient World Ser, 2020)
Cover -- Title Page -- Copyright Page -- Contents -- Notes on Contributors -- Acknowledgement -- Introduction: A 2020 Vision of Plautus -- This Companion -- Retrospection: The Background of Roman Comedy -- Introspection: The Analysis of Plautine Scripts -- Circumspection: The Interaction of Plautine Plays and Roman Society -- Prospection: The Transmission and Reception of Plautus -- Note -- References -- Chapter 1 The State of Roman Theater c. 200 bce -- Sources -- A Well-Established and Cosmopolitan Tradition -- Forms -- Dance to the Tibia -- Improvisatory Farce -- Scripted Drama -- Conclusion -- Further Reading -- References -- Chapter 2 Plautus and Greek Drama -- Menander, Diphilus, and Philemon in Hellenistic Greece -- Traveling Plays: Greek New Comedies in Sicily and South Italy -- Plautus's Bacchides and Menander's Dis Exapaton -- Celebrating Plautus in Antiquity -- Notes -- Further Reading -- References -- Chapter 3 Stages and Stagecraft -- Opposition to a Permanent Theater in Rome -- The Appeal of Temporary Wooden Theaters -- The Comic Potential of the Cavea -- Visualizing the Stage and the Performers -- The Aural Dimension of a Performance -- Conclusion -- Further Reading -- References -- Chapter 4 Actors and Audience -- Plautine Actors and Their Fans -- No Pain, No Gain: The Actors' Life Beyond the Stage -- The Actor's Craft -- A Uorsipellis Audience -- Further Reading -- References -- Chapter 5 Nouo Modo Nouom Aliquid Inuentum: Plautine Priorities -- From Athens to Rome -- A New Manner of Plot(ting) -- A Fresh Roman Concoction -- Conclusion -- Further Reading -- References -- Chapter 6 Plays of Mistaken Identity -- Plautus and the Tradition of Mistaken‐Identity Plays -- Structuring a Series of Misconceptions in Menaechmi and Amphitruo -- Misjudging Alcmena -- Vision, Knowledge, Insanity, and Identity Crisis -- Conclusion -- Notes.